2017
DOI: 10.22436/jnsa.010.02.23
|View full text |Cite
|
Sign up to set email alerts
|

Approximate controllability of impulsive Hilfer fractional differential inclusions

Abstract: In this paper, firstly by utilizing the theory of operators semigroup, probability density functions via impulsive conditions, we establish a new PC 1−ν -mild solution for impulsive Hilfer fractional differential inclusions. Secondly we prove the existence of mild solutions for the impulsive Hilfer fractional differential inclusions by using fractional calculus, multi-valued analysis and the fixed-point technique. Then under some assumptions, the approximate controllability of associated system are formulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…By dividing both sides by n and passing to the limit as n → ∞, we obtain from (9) and (12) that 1 (ηυb 1−γ /Γ(α)) ϕ L p (J,R + ) + h + h/Γ(γ), which contradicts (13). Thus there is a natural number n 0 such that R(B n0 ) ⊆ B n0 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…By dividing both sides by n and passing to the limit as n → ∞, we obtain from (9) and (12) that 1 (ηυb 1−γ /Γ(α)) ϕ L p (J,R + ) + h + h/Γ(γ), which contradicts (13). Thus there is a natural number n 0 such that R(B n0 ) ⊆ B n0 .…”
Section: Resultsmentioning
confidence: 92%
“…The authors in [14] established the existence and uniqueness of global solution in the space of weighted continuous functions for a fractional differential equations involving the Hilfer derivative, the authors in [34] discussed the existence of solutions to nonlocal initial value problems for differential equations with the Hilfer fractional derivative, and the authors in [16] obtained some sufficient conditions to ensure the existence of mild solutions of evolution equation with the Hilfer fractional derivative. In [37], the authors investigated the approximate controllability of Hilfer fractional differential inclusions with nonlocal conditions, the authors in [13] established the approximate controllability of impulsive Hilfer fractional differential inclusions, the author in [24] derived an equivalent definition of the Hilfer derivative, and the authors in [33] studied the controllability of Caputo fractional noninstantaneous impulsive differential inclusions without compactness in reflexive Banach spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Yang et al [41] discussed the approximate controllabil-ity of Hilfer FDEs with nonlocal conditions in a Banach space with the help of semigroup theory, fixed point techniques, and multivalued analysis. Later on, Debbouche et al [14] and Du et al [17] studied the approximate controllability of Hilfer FDEs and semilinear Hilfer FDEs with impulsive control inclusions in Banach spaces, respectively. In 2018, Lv and Yang [34] investigated the approximate controllability of neutral Hilfer FDEs by applying the techniques of stochastic analysis theory and semigroup operator theory in a Hilbert space.…”
Section: Introductionmentioning
confidence: 99%
“…Gu and Trujillo [9] obtained some sufficient conditions to ensure the existence of mild solutions of evolution equation with the Hilfer fractional derivative. Yang and Wang [28,29] investigated existence of mild solutions of Hilfer evolution equations and the approximate controllability of Hilfer fractional differential inclusions with nonlocal conditions and Du et al [7] established the approximate controllability of impulsive Hilfer fractional differential inclusions. Kamocki [13] derived an equivalent definition of the Hilfer derivative and showed that such a derivative is very useful in practical applications.…”
Section: Introductionmentioning
confidence: 99%